Original PaperImpact of phototherapy on selected lipid metabolism indices and oxidation markers in patients with psoriasis vulgaris - Hadas, Ewa; Świętochowska, Elżbieta; Wielkoszyński, Tomasz; Jaroszewska-Smoleń, Jagoda; Jarząb, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Dyslipidaemia occurring concomitantly with psoriasis and proatherogenic serum lipid profile have been observed in multiple studies of middle-aged subjects. Modifications of lipid concentration indices are associated with increased risk of atherosclerosis observed in the course of psoriasis. Aim : To evaluate the impact of phototherapy, taking into consideration its types, on concentrations of selected lipid profile indices, oxidation markers and antioxidant defence of patients with psoriasis vulgaris. Material and methods : The studies included a group of 60 patients with diagnosed psoriasis vulgaris, which for statistical purposes was provisionally divided into three groups of 20 patients each, depending on the type of phototherapy used. All patients underwent 10 therapies using one of three phototherapy methods (UVA, UVB, UVB 311). Results : No significant impact of any of the phototherapy types on concentrations of studied lipid indices was observed. Within the entire study group, phototherapy led to increase of total cholesterol and LDL cholesterol concentrations, but no intensification of oxidation processes was observed after its completion. Conclusions : On the basis of the obtained results it can be concluded that a treatment cycle consisting of ten UV radiation therapies is safe for patients and it does not increase the risk of atherosclerosis in middle-aged psoriatic patients.